Pendampingan Self Declare Sertifikasi Halal pada Pengolah Jamu Loktabat Banjarbaru untuk Meningkatkan Daya Saing Produk - Masrina, Masrina; Ardila, Istiqamah; Musthofa, Khabib; Maharani, Dewi; Lestari, Dinda (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
The loktabat herbal medicine processing group in Banjarbaru City faces significant challenges in improving competitiveness, especially regarding the absence of halal certification. This community service program aims to assist the group in obtaining halal certification through a self-declaration scheme, developing an integrated digital documentation system, and strengthening halal value-based marketing strategies. The implementation method adopts a participatory approach with a focus on two main areas: (1) production and standardization, including halal certification workshops, raw material mapping, and SOP development; and (2) business management and marketing, including the implementation of digital bookkeeping systems and the development of halal branding. The program was implemented for eight months involving 25 active herbal medicine processor. Targeted results include obtaining halal certification within six months, increasing operational efficiency by 30%, implementing a digital documentation system with a 90% adoption rate, and expanding the marketing network through three specialized marketplaces for halal products. This program contributes to strengthening the competitiveness of local MSMEs through product standardization and digitalization of management systems, as well as supporting the achievement of the university's Key Performance Indicators (KPI) in terms of collaboration with the community. The success of this program can be a replication model for the development of other traditional MSMEs in adopting halal standards and modern management systems.